The complete chloroplast genome of Hemisteptia lyrata (Bunge) Fisch. & C. A. Mey. 1836 (Asteraceae) and its phylogenetic analysis - Chun-yan Li; Yan-ping Xing; Wen-juan Hou; Yu-tong Huang; Yan-chang Huang; Yue-yue Song; Ting-guo Kang; Yan-yun Yang; Liang Xu (Mitochondrial DNA. Part B. Resources)
Hemisteptia lyrata, widely distributed in China, has a 152,467 bp chloroplast genome with a large single-copy (LSC) region of 83,473 bp, a small single-copy (SSC) region of 18,594 bp, a pair of inverted repeat regions (IRs) of 25,194 bp in length. The GC content is 36.46%. A total of 133 genes were encoded, of which 88 were protein coding genes, eight were rRNA genes, and 37 were tRNAs. The phylogenetic analysis using the maximum-likelihood method showed that H. lyrata is closely related to the species in Saussurea. This study provides genomic resources for phylogenetic genetics and resource exploitation of H. lyrata.